Criticism of Gender Mainstreaming according to Abdul Karim Zaidan in "Al-Mufassol Fi Ahkam Al-Mar'ah wa Bayt Al-Muslim" - Abbas Sofwan Matlail Fajar; Mara Sutan Rambe (AHKAM : Jurnal Ilmu Syariah, 2019)
AbstractGender Mainstreaming is an action originated from feminism movement closely related to society changes that involves regulation changes, social, economy, politics, and culture. Study about gender issue with all kind of topic that related to religion, especially in Islam, is always catchy to be discussed. In this case, Abdul Karim Zaidan as Islamic jurist in his work “Al-Mufassol Fi Ahkam Al-Mar’ah wa Bayt Al-Muslim” discusses about a life of a woman as a family member as well as a part of society, he carries out academic problem to create an outcome that concern with changing of times, with the aim of reintroducing comprehensively to Moslem women and all Moslems about Islamic Law on women and Islamic household as taught in Islam, and clearly explaining about the rules of life of Moslem women and Moslem family.